Messages : the communications skills book - McKay, Matthew; Davis, Martha, 1947-; Fanning, Patrick (Oakland, CA : New Harbinger Publications, Inc., 2018)
'Many people assume that good communicators possess an intrinsic talent for speaking and listening to others, a gift that can't be learned or improved. The reality is that communication skills are developed with deliberate effort and practice, and learning to understand others and communicate your ideas more clearly will improve every facet of your life. Messages has already helped thousands of people build communication skills and cultivate better relationships with friends, family members, coworkers, and partners. With this fully revised and updated fourth edition, you'll discover new skills to help you communicate your ideas more effectively and become a better listener. Learn how to: Read body language Develop skills for couples communication Negotiate and resolve conflicts Communicate with family members Handle group interactions Talk to children Master public speaking Prepare for job interviews This new edition features a much-needed chapter on digital communication. Effective communication can easily be compromised when you're not able to read your conversation partner's body language, facial expression, or vocal tone. This chapter teaches you how to express yourself well via phone, email, texting, and video--all the skills you need to thrive in the digital age'--
'This classic, best-selling communication skills book has already helped thousands of people cultivate better relationships with friends, family members, coworkers, and partners. Now fully revised and updated, this long-awaited fourth edition of Messages teaches readers to become active listeners, read body language, identify communication styles, practice conflict resolution, improve public speaking skills, and much more. In addition, the book features a new, crucial chapter on digital communication to help readers thrive in the modern world'--
'This book contains supplemental workbook elements used to guide readers and professionals through the informational text and is not an expendable work. Therapists often purchase this format to keep as reference for their practice, administering selected questionnaires to clients as needed. We have been pleased to be part of the CIP program with many similar books in the past, and find the data indispensable for aiding librarians, professionals, and researchers in properly and expediently identifying the material in our books'--
Includes bibliographical references (pages 321-324).
OCLC control number change
Keywords: Communication; PSYCHOLOGY / Interpersonal Relations; LANGUAGE ARTS & DISCIPLINES / Communication Studies; Communication; PSYCHOLOGY / Social Psychology; Electronic books